The European Union and Eastern Mediterranean after Helsinki. CYPRUS – GREECE – TURKEY - Constantinides, Stephanos; Catsiapis, Jean (Études helléniques / Hellenic Studies, 2000)
At the Helsinki Summit (December 10-11, 1999), the Europe of Fifteen bowed to Washington's pressure by reversing the Luxembourg decision of 1997 and accepting Turkey's candidacy for EU membership. Before Helsinki, no candidacy had ever generated the number of problems and debates that Turkey's did. In fact never before had a country with a democratic deficit and a human rights record as poor as Turkey's knocked upon Europe's door. In the past, all states with a history of an authoritarian political régime had to adopt democratic political institutions before applying for EU membership. As did Greece when it drafted its membership application on June 12, 1975, after the fall of the dictatorship in July 1974. All this took place three days after the new Greek republic had passed a constitution comparable to the basic laws of the other EU-member states. In Turkey's case, one year after Helsinki, the Commission in Brussels was obliged to submit to the candidate a 'partnership for membership' oudining the need for constitutional reform, various obligations, e.g. resolving the Kurdish problem and terminating the occupation of Northern Cyprus.